Gender and Social Construction in Local Government: A Experience from Regent of Lebak Regency, Indonesia - Selvi Sulistiani; Ika Arinia Indriyany (Government & Resilience, 2024)
This article dissects how socially constructed society views women in politics as regional heads. Amid the minimal existence of women in politics, women still dare to enter politics to become regional heads. The research results in this article will first explain how social construction translates social roles between women and men, including in the political sphere. Second, this article highlights gender analysis of the leadership style of Iti Octavia Jayabaya as Regent of Lebak from a social construction perspective. With their myriad of problems, women are challenged to enter politics without solid support and political capital. Likewise with Iti Octavia Jayabaya, although her leadership cannot be separated from the existence of a political dynasty, Iti Octavia Jayabaya broke the social construction, which assumes that it is difficult for women to be involved in politics and even become regional leaders. Iti Octavia Jayabaya has proven this through various achievements related to the development of the region he leads to escape it as a disadvantaged region. This research contribution enriches approaches and references regarding the study of women's leadership, to gender issues in government and local politics.